2020
DOI: 10.1093/jisesa/ieaa057
|View full text |Cite
|
Sign up to set email alerts
|

Novel Experimental Methods for the Investigation of Hermetia illucens (Diptera: Stratiomyidae) Larvae

Abstract: Large-scale insect rearing for food and feed production can be improved by understanding diet digestion and host–microbe interactions. To examine these processes in black soldier fly (Hermetia illucens L.; Diptera: Stratiomyidae) larvae, two protocols were developed. Protocol 1 describes a method to produce viable, sterile black soldier fly larvae and a gentle method for diet sterilization. Sterile black soldier fly larvae can be used to study the diverse role of microbes in larval development. Nutrient requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Intact DNA after high-energy beam treatment interfered with further interpretation of bacterial dynamics in the sterile canteen residue. Despite lethal irradiation doses (Gold et al, 2020b), similar bacterial community between sterile and nonsterile canteen waste (Figure 3) after 12 days indicates that some bacterial DNA remained intact and was considered in the bacterial community based on DNA sequencing. As the bacterial communities identified in the sterile canteen waste residue may also include members without any major metabolic functions, these results should be interpreted with caution and are not further discussed.…”
Section: Substrate Microbiota Contributes To Rearing Performancementioning
confidence: 92%
See 1 more Smart Citation
“…Intact DNA after high-energy beam treatment interfered with further interpretation of bacterial dynamics in the sterile canteen residue. Despite lethal irradiation doses (Gold et al, 2020b), similar bacterial community between sterile and nonsterile canteen waste (Figure 3) after 12 days indicates that some bacterial DNA remained intact and was considered in the bacterial community based on DNA sequencing. As the bacterial communities identified in the sterile canteen waste residue may also include members without any major metabolic functions, these results should be interpreted with caution and are not further discussed.…”
Section: Substrate Microbiota Contributes To Rearing Performancementioning
confidence: 92%
“…Irradiation was completed by a commercial provider (Leoni Studer AG, Däniken, Switzerland) with a 10 MeV electron beam (Rhodotron TT300, IBA Corp., Louvain-la-Neuve, Belgium) at a dose of 32 kGy in accordance with the ISO 11137-3:2017 standard [International Organization for Standardization (ISO), 2017]. These treatment conditions produced sterile substrates without microbial growth (Gold et al, 2020b).…”
Section: Food Waste Substratesmentioning
confidence: 99%
“…Alternatively, Gold et al . ( 2020 ) suggested a role of larva-associated microorganisms in providing essential nutrients such as vitamins, because they found that sterile BSF larvae failed to grow on autoclaved substrates, whereas non-sterile larvae were able to grow. We may have missed this effect, because we supplemented vitamins to all substrates and did not test the combination of disinfected eggs on autoclaved substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Substrates with high amounts of proteins, lipids and, in general, substrates complete and balanced in all nutrients, are the best for the development of the BSF and its bioconversion performances [64]. Macronutrients in the substrate can affect the protein content of BSFL, larval weight, bioconversion rate, and development time [65][66][67].…”
Section: Larval Biomass Lipid Content Based On Different Dietmentioning
confidence: 99%